Spectroscopic mapping of the gold complex oligomers (dimer, trimer, tetramer, and pentamer) by excited-state coherent nuclear wavepacket motion in aqueous solutions. Issue 2 (14th December 2022) - Iwamura, Munetaka; Urayama, Rina; Fukui, Airi; Nozaki, Koichi; Liu, Li; Kuramochi, Hikaru; Takeuchi, Satoshi; Tahara, Tahei
Abstract : We investigate excited-state dynamics of the [Au(CN)2 − ] oligomers following photo-initiated intermolecular Au–Au bond formation by carrying out femtosecond time-resolved absorption and emission measurements at various concentrations. Abstract : We investigate the excited-state dynamics of the [Au(CN)2 − ] oligomers following photo-initiated intermolecular Au–Au bond formation by carrying out femtosecond time-resolved absorption and emission measurements at various concentrations (0.080–0.6 mol dm −3 ) with different photoexcitation wavelengths (290–340 nm). The temporal profiles of the time-resolved absorption signals exhibit clear oscillations arising from the Au–Au stretch coherent wavepacket motion of the excited-state oligomers, which is initiated with the photo-induced Au–Au bond formation. The frequency of the observed oscillation is changed with the change of the concentration, excitation wavelength, and wavelength of the excited-state absorption monitored, reflecting the change in the size of the oligomers detected. Fourier transforms (FTs) of the oscillations provide 2D plots of the FT amplitude against the oscillation frequency versus the detected wavelengths. Because the FT amplitude exhibits a node at the peak wavelength of the absorption of the species that gives rise to the oscillation, the 2D plots enabled us to determine the peak wavelength of the excited-state absorption of the dimer, trimer, tetramer, and pentamer. We also performed femtosecond time-resolved absorption measurements for the 0.3 mol dm −3 solution with 260 nm photoexcitation, which is the condition employed in previous time-resolved X-ray studies ( e.g., K. H. Kim et al. Nature, 2015, 518 (7539), 385–389). It was found that various excited-state oligomers, including the dimer, were simultaneously generated under this condition, although the analysis of the previous time-resolved X-ray studies was made by assuming that only the excited-state trimer was generated. The obtained results show that the excited-state dynamics of the trimer claimed based on the time-resolved X-ray data is questionable and that re-analysis and re-examining of its data are necessary.